Numerical Modelling of the Consolidation Behavior of Peat Soil Improved by Sand Columns - Mujah, Donovan; Siaw khur Wee; Tasnim, Sadia (Kluwer Academic Publishers, 2016)
This paper presents a ground improvement method using sand as material in columnar inclusion. The main focus of the study is to model the consolidation behavior of peat soil reinforced by sand columns. The effects of sand column length and column diameter were determined using numerical analysis. It was revealed that the final settlement strongly depends on the area replacement ratio. The numerical results showed that the installation of larger-diameter, fully penetrated columns reduced soil settlement. The settlement reduction results of our numerical analysis are in good agreement with the experimental results. In order to improve the confining stresses of sand, an alternative approach utilizing geogrid encasement was examined numerically. The increasing stiffness of geogrid effectively increased the load carrying capacity of the sand column. Based on the results, geogrid performs better in smaller-diameter columns.